A mixed coating diaphragm and its preparation method and application
By regulating the ratio of inorganic particles to binder and the buried characteristics of polymer microspheres, the problems of poor cohesion and insufficient extrusion resistance of the mixed-coated separator are solved, and higher adhesion and safety performance are achieved.
Patent Information
- Application Number
- CN202411996677.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The mixed-coated diaphragm has poor coating cohesion, poor adhesion and poor extrusion resistance, which leads to powder loss of the diaphragm, easy breakdown and internal micro-short circuit, affecting the safety performance of the battery.
By regulating the relationship between the specific surface area of inorganic particles and the proportion of binder, as well as the buried characteristics of polymer microspheres, the cohesive adhesion and extrusion resistance of the coating are improved to prevent powder loss of the coating.
It improves the cohesive bonding and extrusion resistance of the coating, reduces powder drop rate and short circuit rate, and improves the safety performance of the diaphragm and battery.
Smart Images

Figure CN119786884A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a mixed coating separator and a preparation method and application thereof. Background Art
[0002] The current coating diaphragms include inorganic diaphragms and organic diaphragms. Although the inorganic diaphragms have good mechanical strength and high temperature resistance, their adhesion to the positive and negative electrodes is poor, resulting in problems such as loose fit between the electrode and the diaphragm and soft battery cells. Later, mixed coating diaphragms appeared, that is, mixed coating diaphragms of inorganic particle aluminum oxide and fluorine-free polymer microspheres PMMA, hoping to combine the high temperature resistance of aluminum oxide and the adhesion performance of PMMA.
[0003] However, the mixed coating separator still has problems such as poor coating cohesion, weak adhesion, and poor coating extrusion resistance, which affect product quality. Moreover, weak coating adhesion can easily cause the separator to lose powder during the winding process, causing the separator to be easily punctured during the hot pressure test of the battery cell, and it can also easily cause micro short circuits inside the separator, affecting the safety performance of the battery. Summary of the invention
[0004] In response to the above problems, the present invention provides a mixed coating diaphragm and a preparation method and application thereof, which improves the cohesive bonding force and extrusion resistance of the coating and prevents the coating from falling off by regulating the relationship between the specific surface area of the inorganic particles and the proportion of the binder, as well as the embedding characteristics of the polymer microspheres.
[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0006] The first aspect of the present invention provides a mixed coating membrane, comprising: a base film and a coating layer covering one or both sides of the base film, wherein the coating layer comprises inorganic particles, fluorine-free polymer microspheres and a binder, wherein the inorganic particles are continuously distributed in the coating layer, and the fluorine-free polymer microspheres are discretely distributed in the inorganic particles;
[0007] The specific surface area S of the inorganic particles and the mass ratio M of the binder satisfy the following numerical relationship: S / 0.5≥M≥S / 5, where S is in m 2 / g, M is the percentage of the dry weight of the binder to the total dry weight of the coating layer, in %.
[0008] The following is a detailed description:
[0009] Basement membrane:
[0010] There is no particular restriction on the type of the base film, which can be selected according to actual needs; preferably, the base film can be selected from one or more of polyethylene film, polypropylene film, polyethylene / polypropylene composite film, polyimide film, polyvinylidene fluoride film, polyvinylidene fluoride-hexafluoropropylene film, polyamide film, and polyethylene terephthalate film, preferably a polyethylene film.
[0011] The thickness of the base film may be 4-20 μm, preferably 5-12 μm.
[0012] The porosity of the base film may be 25-70%, preferably 30-65%, and more preferably 35-42%.
[0013] Coating:
[0014] The coating layer comprises inorganic particles, fluorine-free polymer microspheres and a binder;
[0015] Preferably, the inorganic particles are one or more selected from α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide;
[0016] Preferably, the median particle size Dv of the inorganic particles is 50 0.2-1μm, optional 0.2-0.8μm;
[0017] Preferably, the specific surface area S of the inorganic particles is 1-25 m 2 / g.
[0018] The median particle size and specific surface area (BET) of inorganic particles can be measured by a laser particle size analyzer and a specific surface area tester.
[0019] Preferably, the fluorine-free polymer microspheres are one or more selected from polymethyl methacrylate (PMMA), thermoplastic polyurethane elastomer rubber, and polyethylene terephthalate.
[0020] Preferably, the adhesive comprises a first adhesive and a second adhesive;
[0021] The first binder is an acid binder, which may be acrylic acid, polyacrylic acid, or carboxylic acid;
[0022] The second adhesive is an ester adhesive, which may be acrylate, polyacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, or ethyl methacrylate.
[0023] Preferably, based on 100% of the coating layer (dry weight), the coating layer comprises the following components in terms of mass percentage: 80-96% of inorganic particles, 2-12% of a binder, and 3-12% of fluorine-free polymer microspheres;
[0024] More preferably, based on the coating layer (dry weight) as 100%, the coating layer comprises the following components in mass percentage: 80-96% inorganic particles, 1-6% first binder, 1-6% second binder, and 3-12% fluorine-free polymer microspheres.
[0025] The above mass percentages all refer to the dry weight of the above components. The binder and fluorine-free polymer microspheres can also be added in the form of emulsion or solution.
[0026] Preferably, the coating layer has a thickness of 0.1-5 μm.
[0027] The present invention improves the cohesive bonding force and extrusion resistance of the coating by controlling the numerical relationship between the specific surface area S of the inorganic particles and the mass proportion M of the binder so that they satisfy: S / 0.5≥M≥S / 5. When it is too low, mechanical slippage occurs between the coating particles due to extrusion, and the powder loss rate and high-temperature thermal shrinkage are poor. When it is too high, although the cohesive bonding force and extrusion resistance of the coating particles are improved, the coating stacking density is low and the thermal shrinkage is poor.
[0028] M refers to the percentage of the dry weight of the binder in the coating layer to the total dry weight of the coating layer.
[0029] When two binders are used, M is the total mass ratio of the first binder and the second binder, that is, the percentage of the total dry weight of the first binder and the second binder to the total dry weight of the coating layer.
[0030] It should be noted that the above relationship is in S units m 2 When the unit of M is %, the relationship between the substituted values (without units) is shown.
[0031] In the embodiment of the present invention, the embedding depth of the fluorine-free polymer microspheres in the coating layer is h>H*1 / 2, where H is the thickness of the coating layer; and / or, the embedding depth h satisfies: Dv 50 / 3≤h≤Dv 50 , where Dv 50 It represents the median particle size of fluorine-free polymer microspheres. Figure 1 shown.
[0032] The embedding depth h is the vertical distance between the bottom of the fluorine-free polymer microsphere and the outer surface of the coating layer, which is a statistical average value.
[0033] Preferably, the embedding depth h of the fluorine-free polymer microspheres in the coating layer is 1.5-2.5 μm, and the median particle size Dv of the fluorine-free polymer microspheres is 50 2-3μm.
[0034] In the embodiment of the present invention, the percentage of the number of the fluorine-free polymer microspheres protruding from the surface of the coating layer to the total number of all the fluorine-free polymer microspheres is 15-90%, preferably 15-80%, and more preferably 48-70%.
[0035] In an embodiment of the present invention, the peel strength of the mixed-coated separator is greater than 80 N / m.
[0036] In an embodiment of the present invention, the heat shrinkage rates of the mixed-coated separator in the machine direction MD and the transverse direction TD after being kept at 130° C. for 1 hour are both less than 5%.
[0037] The thermal shrinkage rate can be tested by a method known in the art. As a specific example, the test is performed according to the requirements of GB / T36363-2018.
[0038] In the embodiment of the present invention, the powder loss rate of the mixed-coated separator is ≤2.2%, preferably ≤0.5%.
[0039] The powder loss rate is the powder shedding loss rate of the mixed coating membrane after physical friction.
[0040] In the embodiment of the present invention, the compression rate of the mixed-coated diaphragm is 0.6-2.5%.
[0041] The compression ratio refers to the thickness change rate of the diaphragm before and after hot pressing.
[0042] The mixed-coating diaphragm coating of the present invention has high cohesion, high peel strength, good coating extrusion resistance, is not prone to powdering, and has good safety performance.
[0043] A second aspect of the present invention provides a method for preparing a mixed coating membrane, comprising the following steps:
[0044] Dispersing inorganic particles, fluorine-free polymer microspheres and a binder in a solvent, and mixing them evenly to obtain a coating slurry;
[0045] Applying the coating slurry on at least one side of the base film and drying it to obtain a mixed coating separator;
[0046] The coating slurry comprises the following components in mass percentage, based on the dry weight of the coating slurry being 100%: 80-96% of inorganic particles, 2-12% of a binder, and 3-12% of fluorine-free polymer microspheres; the coating slurry has a viscosity of 20-200 mPa·s;
[0047] The specific surface area S of the inorganic particles and the mass ratio M of the binder satisfy the following numerical relationship: S / 0.5≥M≥S / 5, where S is in m 2 / g, the unit of M is %.
[0048] Preferably, the adhesive comprises a first adhesive and a second adhesive, and the mass ratio of the first adhesive to the second adhesive is 1-6:1-6, preferably 1:1.
[0049] Preferably, the solvent is at least one selected from water, N-methylpyrrolidone, and N,N-dimethylacetamide.
[0050] Preferably, the mixing speed is 800N2000rpm, and the mixing time is 20N100min.
[0051] In addition to the above raw materials, the coating slurry may also contain other arbitrary components, such as viscosity modifiers, dispersants, wetting agents, electrolyte dispersion inhibitors, etc. The above components are not particularly limited as long as they do not cause adverse effects on the lithium battery, and the above arbitrary components may be one, two or more.
[0052] There is no particular restriction on the coating method of the slurry, and coating methods such as coating method and dipping method can be selected for coating. As coating methods, methods such as scraper method, reverse roll method, direct roll method, micro gravure roll method, extrusion method, spraying method, and spot coating method can be cited. Considering the uniformity of the thickness of the porous film, it is preferred that the micro gravure roll method is used for coating.
[0053] There is no particular limitation on the drying method, and drying methods such as hot air, low-humidity air, vacuum drying, spray drying, and freeze drying can be selected.
[0054] The present invention adjusts the coating raw material ratio and the relationship between the specific surface area S of the inorganic particles and the mass proportion M of the binder, and further ensures the viscosity of the slurry to regulate the embedding depth of the microspheres and the proportion of the number of protruding coatings, thereby achieving the purpose of improving the cohesive bonding force and extrusion resistance of the coating and reducing the powder loss rate and short circuit rate.
[0055] According to the method provided in the second aspect of the embodiment of the present invention, a mixed-coating diaphragm according to any embodiment of the first aspect of the present invention can be obtained.
[0056] A third aspect of the present invention provides a use of the above-mentioned mixed coating separator in the preparation of a secondary battery.
[0057] The mixed coating separator provided in the embodiment of the present invention can be used in different types of batteries, so there is no particular restriction on the type of battery, and it can be selected according to actual needs. Preferably, it can be used in secondary batteries, especially secondary batteries containing liquid electrolytes, such as lithium ion batteries, sodium ion batteries, etc.
[0058] Beneficial effects:
[0059] The present invention improves the cohesive force and extrusion resistance of the coating by regulating the relationship between the BET of inorganic particles and the total mass proportion of the binder and the embedding depth of the polymer microspheres, prevents the coating from falling off, and improves the safety performance of the diaphragm and the battery.
[0060] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 Schematic diagram of the embedding depth of fluorine-free polymer microspheres in the coating layer. DETAILED DESCRIPTION
[0062] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0063] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0064] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0065] Test method:
[0066] The samples were cut by cryo-ion beam cutting instrument and the cross sections were observed by SEM.
[0067] Embedding depth: Cut 10 coated membrane samples of 5 cm × 5 cm, of which 5 were cut vertically along the TD direction, and the other 5 were cut vertically along the MD direction. Use Zeiss field emission scanning electron microscope (ZEISSSIGMA300 under 500 times electron microscope field of view) or super depth of field microscope (Keyence, VHX-7000N under 500 times electron microscope field of view) to observe the cross section, measure the vertical distance between the bottom of the PMMA microsphere and the outer surface of the coating within the range of the microscope, record it as the embedding depth h, and take its average value.
[0068] The percentage of PMMA microspheres protruding from the coating surface (the percentage of PMMA microspheres protruding from the coating surface to the total number of fluorine-free polymer microspheres): 10 5 cm × 5 cm membrane samples were cut, 5 of which were cut vertically along the TD direction. A Zeiss field emission scanning electron microscope (ZEISS SIGMA 300, 500 times the field of view of the electron microscope) was used to observe the range of the microscope. The number of PMMA microspheres was recorded as n1, the number of PMMA microspheres protruding from the outer surface of the ceramic coating was recorded as n2, and the percentage of PMMA microspheres protruding from the outer surface of the ceramic coating in the TD direction was n. TD =n2 / n1, repeat the test for 5 groups of samples and take the average value; the other 5 samples were cut vertically along the MD direction and observed using a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 under a 500x electron microscope field of view). The number of PMMA microspheres within the viewing range was recorded as n3, the number of PMMA microspheres protruding from the outer surface of the ceramic coating was recorded as n4, and the proportion of PMMA microspheres protruding from the outer surface of the ceramic coating in the MD direction was nM. D = n4 / n3, repeat the test for 5 groups of samples and take the average value, then the proportion of microspheres protruding from the outer surface of the ceramic coating = (n TD +n MD ) / 2.
[0069] Peel strength: Use a 2.5cm×30cm mold to cut the sample, stick the double-sided adhesive paper for peel strength to the test board, tear off the surface sticker, keep about 2cm of sticker, stick the sample coating surface flat to one end of the double-sided adhesive sticker, roll back and forth three times with a roller, peel off 1cm manually to make a sample strip to be tested, clamp the end with the residual sticker on the lower chuck of the tensile machine, and clamp the other end of the sample strip to the upper chuck (the distance between the clamps is (100±5)mm), ensuring that there is no tilt, and the tensile speed is 50mm / min. The average of the three measurements is taken;
[0070] Heat shrinkage rate: Cut a sample of 10 cm × 10 cm in size, mark the transverse TD and longitudinal MD on the sample, measure the transverse and longitudinal widths with a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C), clamp the sample between two sealed A4 papers, place the sample in a 130°C oven for 1 hour, and measure the transverse and longitudinal widths with a fully automatic image measuring projector after the sample returns to room temperature. Measure 3 times and take the average value. The heat shrinkage rate can be calculated by the following formula: MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100; TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) ÷ TD length before heating × 100;
[0071] Powder loss rate: Cut the membrane sample to be tested into 6 pieces, 3cm×22cm in size, place them on an analytical balance and weigh them, and record the weight as ml; ensure that the curved table of the friction color fastness tester (Daei Science Seiki Manufacturing Co., Ltd., RT-300S) is clean, fix the lens paper on the friction head of the friction color fastness tester, where the smooth side of the lens paper faces outward, and then fix the cut battery membrane on the curved table of the friction color fastness tester, with one side of the coating facing up, clamp it and gently place the friction head on the membrane, set the number of experiments to 5 on the operation panel of the color fastness tester and click to start. After the experiment is completed, take out the battery membrane, place it on an analytical balance and weigh it, and record the weight as m2. Powder loss amount M (mg) = m1-m2, take the average value of the six groups of membrane test data. Powder loss rate = M / m1×100%, if the membrane is a double-layer coating on both sides of the base membrane, the powder loss rate on each side meets the requirements.
[0072] Compression rate: Cut the sample film into 50*50mm square samples, stack 5 cut samples together and use Mahr thickness gauge (Mahr model: C1202) to measure the thickness at 10 points, and take the average value as D0; then cut the PET sheet into 50*50mm square sheets, place the sample film between the two cut PET sheets and align them, and place them in a hot press (Qmesys, QM940AS) for hot pressing; the hot pressing parameters are set to 1000kgf, 70℃, and the holding time is 1s. After taking out, measure 10 points of the hot-pressed diaphragm, and take the average value as D1, then the compression rate 100%.
[0073] Examples 1 to 10, Comparative Examples 1 to 2
[0074] Boehmite, PMMA emulsion (SWA709, solid content 20% from Shenzhen Haodian Technology Co., Ltd.), polyacrylic acid emulsion (LIB-S105B, solid content 21% from Hunan Gaorui Power Material Co., Ltd.), polyacrylate emulsion (BM-900B, solid content 40% from Japan ZEON Co., Ltd.), sodium carboxymethyl cellulose, polyether-modified siloxane and water were stirred at 1300 rpm for 60 min to prepare an aqueous coating slurry;
[0075] The aqueous coating slurry was gravure coated on one side of a polyethylene base film (thickness 9 μm, porosity 39%) by an MCD coater, and finally dried in an oven at 70° C. for 12 seconds to obtain a mixed coating separator.
[0076] The structure and performance of the diaphragm were tested according to the above test methods.
[0077] The preparation parameters and test results of each embodiment and comparative example are shown in Table 1.
[0078] Table 1
[0079]
[0080]
[0081] From the comparison of Examples 1 to 10 and Comparative Examples 1-2, it can be seen that when the specific surface area S of the inorganic particles and the mass ratio M of the binder do not satisfy the limitation of S / 0.5≥M≥S / 5, it is impossible to simultaneously take into account a larger peel strength, a smaller thermal shrinkage rate, a smaller powder loss rate and a smaller compression rate.
[0082] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A mixed coating diaphragm, characterized in that: include: A base film and a coating layer covering one or both sides of the base film, wherein the coating layer comprises inorganic particles, fluorine-free polymer microspheres and a binder, wherein the inorganic particles are continuously distributed in the coating layer, and the fluorine-free polymer microspheres are discretely distributed in the inorganic particles; The specific surface area S of the inorganic particles and the mass ratio M of the binder satisfy the following numerical relationship: S / 0.5≥M≥S / 5, where S is in m 2 / g, M is the percentage of the dry weight of the binder to the total dry weight of the coating layer, in %.
2. The mixed-coating separator according to claim 1, characterized in that: The embedding depth of the fluorine-free polymer microspheres in the coating layer is h>H*1 / 2, wherein the contact surface between the coating layer and the base film is the inner surface, the other opposite surface is the outer surface, the vertical distance between the bottom of the fluorine-free polymer microspheres and the outer surface is the embedding depth h, and the thickness of the coating layer is H.
3. The mixed coating diaphragm according to claim 2, characterized in that: The embedding depth h satisfies: 50 / 3≤h≤Dv 50 , where Dv 50 It represents the median particle size of the fluorine-free polymer microspheres.
4. The mixed-coating separator according to any one of claims 1 to 3, characterized in that: The percentage of the number of the non-fluorinated polymer microspheres protruding from the surface of the coating layer to the total number of all the non-fluorinated polymer microspheres is 15 to 90%.
5. The mixed-coating separator according to any one of claims 1 to 3, characterized in that: The peel strength of the mixed-coated separator is greater than 80 N / m; and / or The heat shrinkage rates of the mixed-coated separator in the machine direction MD and the transverse direction TD after being kept at 130° C. for 1 hour were both less than 5%.
6. The mixed-coating separator according to any one of claims 1 to 3, characterized in that: The powder loss rate of the mixed coating separator is ≤2.2%; and / or The compression rate of the mixed-coated diaphragm is 0.6-2.5%.
7. The mixed-coating separator according to any one of claims 1 to 3, characterized in that: The binder comprises a first binder and a second binder, and the coating layer comprises the following components in mass percentage: 80-96% inorganic particles, 1-6% first binder, 1-6% second binder, and 3-12% fluorine-free polymer microspheres.
8. A method for preparing a mixed coating membrane according to any one of claims 1 to 7, characterized in that: The following steps are involved: Dispersing inorganic particles, fluorine-free polymer microspheres and a binder in a solvent, and mixing them evenly to obtain a coating slurry; Applying the coating slurry on at least one side of the base film and drying it to obtain a mixed coating separator; The coating slurry comprises the following components in mass percentage, based on the dry weight of the coating slurry being 100%: 80-96% of inorganic particles, 2-12% of a binder, and 3-12% of fluorine-free polymer microspheres; the viscosity of the coating slurry is 20-200 mPa·s; The specific surface area S of the inorganic particles and the mass ratio M of the binder satisfy the following numerical relationship: S / 0.5≥M≥S / 5, where the unit of S is m2 / g and the unit of M is %.
9. The preparation method according to claim 8, characterized in that: The binder comprises a first binder and a second binder, and the mass ratio of the first binder to the second binder is 1-6:1-6.
10. Use of the mixed coating separator according to any one of claims 1 to 7 in preparing a secondary battery.